Identities and Strangeness. Ramblings from Zygmunt Bauman (Andamios, Revista de Investigación Social, 2011)
This article pretends to reflect about Identities and Strangeness in modern contemporary societies taking as crucial axis the latest books by polish sociologist Zygmunt Bauman, and as main thread one of the main characters of G.W. Sebalds’s novel Austerlitz. In concordance with the “elective affinities” between Sociology an Literature, as posed by Bauman, the text also reflects about other problems: uprootedness, mobility, and voyages as distinctive metaphors of our time.
Keywords: Identities; strangeness; voyages; mobility; uprootedness